Caracterização de cadeia de isoladores de ultra alta tensão para torres de transmissão de corrente contínua - Cagido, Mayara Cunha (2019)
This work presents a study about the withstand characteristics of a ultra high voltage insulators string in direct current transmission towers, focusing on the voltage waveforms analysis measured throughout lightning impulses, based on the Leader Progression Model - LPM. By describing the study of the discharge process, voltage impulse types, relevant time parameters of electrical tests and equations that describe the LPM-based disruption process, it was possible to gather the necessary knowledge for the realization of this work. With the experimental results, obtained with the application of lightning impulses, it was possible to compare the data and the formulations developed for the LPM. Tests with switching impulses and current measurements of the Ultra High Voltage laboratory - UHV at Electrical Energy Research Center - Cepel were also performed to improve the research and to promote a better understanding of the operation of the laboratory. The tests performed provided important information about the insulators string, like the time parameters of the experimental results, their relation with the calculations for other types of air gaps and the complexity of performance and test measurements, contributing to the research and development of the UHV Laboratory, unique in Latin America.